2016
DOI: 10.12659/pjr.897937
|View full text |Cite
|
Sign up to set email alerts
|

Urethroscrotal Fistula: A Rare Cause of Scrotal Swelling

Abstract: SummaryBackgroundUrethroscrotal fistula (USF) is an abnormal communication between the urethra and the scrotum. This rare abnormality may be iatrogenic or secondary to perforation of the urethra by a stone. After the passage of urine to the scrotum through the fistula, painless scrotal swelling develops, which disappears completely with manual compression, and voiding can be maintained in this way. Retrograde urethrography (RU) and voiding cystourethrography (VCU) are traditional diagnostic methods, but they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…7 Parlak et al also reported a case of uretheroscrotal fistula that developed after a surgery for uretheral stone removal and cystolithotomy, patient presented with painless scrotal swelling that used to disappear after manual compression, little bit similar as in our case fistula developed after scrotal stone removal but swelling didn't disappear on manual compression but demonstrated clear evidence of scrotourethral fistula as fluid was coming out both from scrotal skin and the urethral meatus (Figure 4), so we made a diagnosis of scrotourethral fisula on clinical basis only, unlike in prior case where they prescribed multidetector CT(MDCT) for the diagnosis. 8 Stizzo et al also reported a case of uretheroscrotal fistula associated with scrotal abscess, fistula developed because of wrong catheterization and because of this fistula scrotal abscess drained and helped in prevention from developing into fourneier's gangrene. 9 But in our case no scrotal abscess or any other symptoms found other than a scrotal swelling.…”
Section: Discussionmentioning
confidence: 97%
“…7 Parlak et al also reported a case of uretheroscrotal fistula that developed after a surgery for uretheral stone removal and cystolithotomy, patient presented with painless scrotal swelling that used to disappear after manual compression, little bit similar as in our case fistula developed after scrotal stone removal but swelling didn't disappear on manual compression but demonstrated clear evidence of scrotourethral fistula as fluid was coming out both from scrotal skin and the urethral meatus (Figure 4), so we made a diagnosis of scrotourethral fisula on clinical basis only, unlike in prior case where they prescribed multidetector CT(MDCT) for the diagnosis. 8 Stizzo et al also reported a case of uretheroscrotal fistula associated with scrotal abscess, fistula developed because of wrong catheterization and because of this fistula scrotal abscess drained and helped in prevention from developing into fourneier's gangrene. 9 But in our case no scrotal abscess or any other symptoms found other than a scrotal swelling.…”
Section: Discussionmentioning
confidence: 97%
“…Urethral fistula is a rare occurrence in men. [ 1 2 ] They may be congenital or acquired, and possibly caused include infection, inflammatory disease, neoplasm, congenital condition, trauma and iatrogenic injury. [ 1 ] Paraplegic patient has a higher risk of urethral fistula due to prolonged urinary catheterizations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] They may be congenital or acquired, and possibly caused include infection, inflammatory disease, neoplasm, congenital condition, trauma and iatrogenic injury. [ 1 ] Paraplegic patient has a higher risk of urethral fistula due to prolonged urinary catheterizations. [ 1 ] In a patient with paraplegia that treated with long-term catheterization, as in our case, we hypothesized that prolonged catheterization during the course of the primary disease, sensory disturbance and chronic immobilization might lead to pressure necrosis in the urethral wall and finally result in the formation of urethroscrotal fistula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations